Differences effect of the application the discovery learning and problem based with GeoGebra to improve critical thinking ability / Irvan Irvan - Irvan, Irvan (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2023)
The purpose of the research know and analyze the different effects of the application of Discovery Learning and Problem Based Learning models administered by GeoGebra to improve students' critical thinking. The research method used was trial research applied to two classes with a Discovery learning and Problem Based Learning model, each of the learning assisted by GeoGebra. The research results were analyzed using descriptive and inferential analysis. The first trial class's average critical thinking ability was 82.00, and the second practical class was 84.64, more significant than the specified KKM, 70, Based on the results of the descriptive study. So that Discovery Learning and Problem Based Learning with GeoGebra positively influence students' critical thinking skills. But, there is no difference in the practical application of the two learning models.